Muhammadiyah's Educational Philanthropy Movement in North Kolaka - Muhammad Alifuddin; Suarni Suarni; Nurjannah Nurjannah (Institut Agama Islam Negeri (IAIN) Kendari, 2020)
This study aims to provide an analytical view of the Muhammadiyah Education Philanthropy Movement in North Kolaka. The research data was obtained through a series of in-depth interviews, observations and document studies. All data obtained was assessed in stages using the Miles and Huberman analysis models.Based on data’s found in the field of research, the Muhammadiyah educational philanthropy movement has existed in this region since 1968. The Muhammadiyah philanthropy movement in North Kolaka is a social fact that is inevitable to be appreciated. Imagine, the movement of social movements has been present in a social space that was historically geographically isolated and prone to historically political politics. In such limited conditions, in a period where the eyes of social movements are generally still